Bahasa Inggris - RM Anto Harprianto; Reiza D. Dienaputra; Kevin Muhamad Lukman; Awaludin Nugraha (Universitas Negeri Jakarta, 2025)
Rural tourism sustainability relies heavily on community competence, yet significant skill gaps among residents remain a critical barrier. This study aims to systematically synthesize the role and models of Non-Formal Education (NFE) in developing tourism village potential. Employing a Scoping Review methodology, twenty-one (21) articles published between 2016 and 2025 were analyzed based on specific inclusion criteria regarding NFE in rural contexts. The review identifies three dominant NFE intervention models: (1) Economic Empowerment (vocational training), (2) Socio-Cultural Preservation (heritage education), and (3) Institutional Capacity Building (governance strengthening). These interventions are proven to essentially transform passive residents into skilled tourism actors. However, this study is limited to academic literature and may exclude practical insights from non-published field reports. Consequently, it is recommended that stakeholders integrate standardized NFE curricula into village policy to ensure consistent human resource development.